KINERJA BADAN KEPEGAWAIAN DAERAH DALAM PERCEPATAN PENGALIHAN STATUS KEPEGAWAIAN KABUPATEN/ KOTA KE PROVINSI DI PROVINSI PAPUA BARAT PASCA BERLAKUNYA UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Deasy Agustina Tulus (Jurnal Ilmiah Wahana Bhakti Praja, 2018)
The process of transferring the employment status of employees from Regency / City to Province as a follow-up of Law Number 23 of 2014 concerning Regional Government, and Circular of the Minister of Home Affairs Number: 120/253 / SJ dated January 16, 2015 concerning Organizing Government Affairs After being determined Law Number 23 of 2014, Circular of the Minister of Home Affairs Number: 120/5935 / SJ dated October 16, 2015 concerning Acceleration of Transfer of Affairs Based on Law Number 23 of 2014. Regional Personnel Board of West Papua Province as executor of governmental affairs in West Papua Province has the responsibility to carry out the transfer of employee employment status. This study aims to determine and analyze the performance of the West Papua Province Personnel Agency in accelerating the transfer of Regency / City employment status to the Province, knowing and analyzing the supporting and inhibiting factors of performance and analyzing the efforts in improving performance. This study aims to determine and analyze the performance of the West Papua Province Personnel Agency in accelerating the transfer of Regency / City employment status to the Province, knowing and analyzing the supporting and inhibiting factors of performance and analyzing the efforts in improving performance. The method used in this study is a qualitative method, data collection techniques used are interviews, observation and documentation.The theory used in this study is the performance theory put forward by Wibowo namely Productivity, Quality, Timeliness, Cycle Time, Utilization of Resources, and Costs, and the theory of inhibiting and supporting factors as well as Efforts proposed by Stephen P. Robbins. The method used in this study is a qualitative method, data collection techniques used are interviews, observation and documentation.The results showed that the performance of the Regional Personnel Board of West Papua Province was good enough, but there were still some obstacles such as the utilization of human resources that were still low, the use of personnel service system (SAPK) which was still low, lack of socialization about the employment status, and limitations budget. Therefore, in the study the authors conveyed several efforts to improve the performance of the Agency, such as budgeting the status transfer activities again, utilizing available technology, increasing the capacity of human resources.